Low concentrations of recombinant activated factor VII normalize coagulation patterns by reversing the changes in viscoelastic testing parameters induced by abelacimab in vitro - Yasser Khder; Serge Côté; Klaus Peter Hoffmann; Debra Freedholm; Dan Bloomfield; Jean M. Connors (Research and Practice in Thrombosis and Haemostasis)
Background: Low doses of recombinant activated factor (F)VII (rFVIIa), used to manage bleeding in patients with severe FXI deficiency, have been proposed to bypass effects of the FXI/FXIa inhibitor abelacimab. Objectives: To test whether low concentrations of rFVIIa could abolish changes in coagulation parameters induced by abelacimab as measured by rotational thromboelastometry. Methods: Whole blood specimens obtained in citrated tubes from 6 healthy donors were incubated with 15 and 30 μg/mL of abelacimab or vehicle for 10 minutes at 37 °C. Specimens were subsequently spiked with rFVIIa at 0.5 and 1 μg/mL or vehicle. Clot formation was monitored using rotational thromboelastometry delta analyzers and the nonactivated thromboelastometry test. Clotting time (CT, in seconds), clot formation time (CFT, in seconds), α angle, etc. were measured and compared with vehicle (excipient solution containing His/His-HCl, sucrose, polysorbate 20 solution) and reference ranges provided by the manufacturer. Results: Abelacimab at 15 and 30 μg/mL concentrations increased CT by 61% and 64%, CFT by 37% and 32%, and decreased α angle by 10% and 14% compared with baseline, respectively. Adding rFVIIa at 0.5 and 1.0 μg/mL shortened CT by 21% and 38%, CFT by 33% and 49%, and increased α angle by 29% and 47%, respectively. Nonactivated thromboelastometry parameters generally remained within normal reference ranges when rFVIIa was added. Conclusion: Low concentrations of rFVIIa (0.5-1 μg/mL) corrected the effects of abelacimab as assessed by rotational thromboelastometry. Our data support using low doses of rFVIIa for bleeding management in patients treated with abelacimab.